Resolving cross-shelf dynamics in the Agulhas Current from GlobCurrent and glider observations - Maja, Tumelo (Department of Oceanography, 2020)
The Agulhas Current is the strongest Western Boundary Current of the Southern Hemisphere and it plays a significant role in the circulation of the shelf and coastal waters, whereby mesoscale (50- 500 km) and submesoscale (1 -10 km) instabilities in the Agulhas Current impact the local oceanography of the shelf region. The main objective of this study is to evaluate the ability of a gap-free and merged gridded satellite ocean current dataset, GlobCurrent, to resolve and monitor the variability of the Agulhas Current’s cross-shelf dynamics. In this study, GlobCurrent is compared to in-situ observations collected from underwater gliders through mapping and correlation analysis to assess the product’s accuracy in different subdomains and water depths of the Agulhas Current’s main area domain. We also investigate the value of using a higher resolution satellite and gap-free Sea Surface Temperature (SST) dataset to complement the GlobCurrent dataset in observing the Agulhas Current’s flow processes and features. The results show that GlobCurrent is adequate for describing large mesoscale features and deep water flows but the product has limitations in capturing fast-evolving and small mesoscale features, particularly the Durban Eddy in the KZN bight region. GlobCurrent also exhibits, at times, directional errors in addition to the current speed discrepancies. This research study demonstrates the limitation of the GlobCurrent product for monitoring ocean current variability in shallow, coastal waters and regions dominated by small mesoscale variability. This study also provides new insights on the joint use of other merged satellite products i.e. merged ODYSSEA SST, which may compensate for some of the GlobCurrent product’s shortfalls. Future studies should consider complementing altimetry-based satellite products like GlobCurrent with other merged satellite observation products such as ODYSSEA SST for better imaging of small mesoscale processes and features in shallow coastal waters.